Aliança AMARTE: A Collaborative Network to Improve Oncologic Pediatric Care in Brazil - Lopes, Luiz Fernando; Loggetto, Patrícia; de Oliveira, André; Farias, Bruna; Nunes, Carla; de Almeida, Aline Esmeraldo Andrade; do Amaral, Anna Beatriz Costa Neves; Frisanco, Anita; Fiori, Carmem Maria Costa Mendonça; Santana, Daniela; Gasperini, Débora Garcia [UNESP]; Francelino, Eliane; et al. (Wiley, 2025)
INTRODUCTION: In Brazil, inequalities in access to treatment and survival of childhood cancer are observed across different geographic regions. In 2014, under the coordination of Hospital de Câncer Infantojuvenil de Barretos (Fundação Pio XII), six hospitals met weekly for case discussion. In 2019, the AMARTE (Apoio Maior Aumentando Recursos e Treinamentos Especializados) Alliance officially began with the aim to improve the quality of pediatric oncology care in Brazil and became a collaborative network of innovation, research, and learning with 31 member institutions in 2024. METHODS: AMARTE follows four strategic pillars: (1) equalize diagnostics, (2) homogenize treatment, (3) epidemiological and survival studies, and (4) scientific development and innovation. Fundação Pio XII and St. Jude Children's Research Hospital provide infrastructure and human resources. Implementation resources are supported mainly by the member institution. The first strategic goal was to maintain sustainable member engagement. A semestral assessment (SCORE) monitors the progress and engagement level, based on defined indicators. RESULTS: Three engagement reports have been published, with an increase in members' scores: 17 hospitals increased their SCORE, 7 decreased, and 1 hospital did not change. Key achievements include a common data registry, diagnostic and treatment protocols, regular technical-scientific meetings, and the formation of a fundraising group to achieve financial sustainability. CONCLUSION: The first decade of the AMARTE Alliance highlights the relevance of collaboration in pediatric oncology. Challenges refer to the sustainable participation of specialists and heterogeneous governance structure across members, requiring flexibility in the implementation of shared initiatives. Outcome indicators are being developed to assess long-term impact.